Between Recognition and Neglect: An Assessment of the Yazidi Survivors Law in Iraq's Reparation for Genocide Victims in Light of International Standards - Omar , Dzhwar; Nasser, Dima (Journal of Legal Sciences, 2026)
This research analyzes the Yazidi Female Survivors Law (2021) as landmark legislation for compensating victims of sexual violence and genocide in Iraq, aiming to assess its compliance with comprehensive reparations principles under international standards. The core problem lies in the procedural hurdles and legislative constraints that impede the realization of full justice. The most significant finding is that while the law achieved symbolic recognition and partial financial reparations, it faced severe procedural limitations (such as mandating a criminal complaint) and a legal conflict over granting identity to survivors’ children, undermining the full restitution of their rights. Consequently, the most critical recommendation is directed at the Iraqi Legislator to abolish the criminal complaint requirement and adopt the principle of good faith to ease the burden of proof, and at the International Community to provide support for resolving the civil identity issues of survivors’ children to secure their rights.